QuickCount ® : A novel automated software for rapid cell detection and quantification - Tiong, Kai Hung; Chang, Jit Kang; Pathmanathan, Dharini; Fadlullah, Muhammad Zaki Hidayatullah; Yee, Pei San; Liew, Chee Sun; Rahman, Zainal Ariff Abdul; Beh, Kheng Ling; Cheong, Sok Ching (Future Medicine, 2018)
We describe a novel automated cell detection and counting software, QuickCount ® (QC), designed for rapid quantification of cells. The Bland–Altman plot and intraclass correlation coefficient (ICC) analyses demonstrated strong agreement between cell counts from QC to manual counts (mean and SD: -3.3 ± 4.5; ICC = 0.95). QC has higher recall in comparison to ImageJ auto , CellProfiler and CellC and the precision of QC, ImageJ auto , CellProfiler and CellC are high and comparable. QC can precisely delineate and count single cells from images of different cell densities with precision and recall above 0.9. QC is unique as it is equipped with real-time preview while optimizing the parameters for accurate cell count and needs minimum hands-on time where hundreds of images can be analyzed automatically in a matter of milliseconds. In conclusion, QC offers a rapid, accurate and versatile solution for large-scale cell quantification and addresses the challenges often faced in cell biology research.